GÊNERO E SEXUALIDADE ATUANDO NA CONSTRUÇÃO DISCURSIVA DAS MASCULINIDADES - Brito, Milena Ximenes (Intercâmbio, 2010)
Based on a socioconstrucionist view of discourse and on positioning theory, this paper investigates how gender and sexuality are used in the construction of meanings related to male gender identities. The data point to the essentialiazation of traditional traits attributed to male and female genders.